Polemik Penyaluran Bantuan Sosial di Masa Pandemi yang terjadi di Provinsi Sumatera Selatan - Cellia Calysta; Sakir Ridho Wijaya; Fairuz Arta Abhipraya (Departemen Ilmu Pemerintahan Fisip Unhas, 2022)
The distribution of Social Assistance Funds in Indonesia has always been an absolute legal problem, especially during the current Pandemic. The policy carried out by the government in the distribution of Social Assistance has had a major influence on the community due to the existence of a government policy that implements the Lockdown or PSBB system to reduce the spread of the Covid-19 virus. We see that not a few Indonesians especially Provinces Sumatera Selatan work as online motorcycle taxis, traders, and other odd jobs who have middle to lower incomes. Therefore, the government should facilitate or provide social assistance to communities affected by the Lockdown or PSBB that has been implemented. The government must also pay attention to the price of affordable food needs, especially for people with low income. In this article, I try to explain a little about the pandemic that occurred in South Sumatra Province, whether it has been evenly distributed or not. This research uses qualitative methods with descriptive techniques and data collection through literature studies. The results of this study indicate that the distribution of social assistance has not been implemented properly and evenly. The impact of this polemic is the existence of injustice to the middle and lower class of society.